Sintesis Copper-Nanoparticles dari Limbah Leaching Kalkopirit Sebagai Zat Antibakteri dengan Metode Reduksi - Wibowo, Decka Pynka; Kusumastuti, Yuni; Prasetya, Agus; Asih, Yekti; Petrus, Himawan T.B.M; Idrus, Arifudin (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Nanoparticle technology has been widely used in various industries because of its advantages in particle size control systems. One example of the use of nanoparticle technology is copper nanoparticles as an antibacterial material. This research focuses on the utilization of leaching waste as a material for the synthesis of copper nanoparticles. The synthesis of copper nanoparticles was carried out by chemical reduction method between chalcopyrite stone leaching waste namely CuSO4 as precursor, Cetyl Trimethyl Ammonium Bromide (CTAB) as surfactant and NaBH4 reducing agent. The synthesized material will be analyzed using UV-Vis spectroscopy. Furthermore, the particle size will be estimated using PSA and its antibacterial properties will be analyzed using the well diffusion method by looking at the effectiveness of the inhibitory power against Escherichia coli FNCC 0049 and Staphylococcus bacteria aureus FNCC 0047. The results of the synthesis obtained the smallest size of 235.7 nm from the ratio of precursor concentration, reducing agent concentration and, a surfactant concentration of 1:20:8. The results of the synthesis of copper nanoparticles with concentrations of 10.000 ppm showed the presence of inhibitory power to overcome Escherichia coli FNCC 0049 and Staphylococcus bacteria aureus FNCC 0047.